Financial statistics and data analytics - Shuangzhe Liu; Milind Sathye (MDPI, 2021)
Modern financial management is largely about risk management, which is increasingly data-driven. The problem is how to extract information from the data overload. It is here that advanced statistical and machine learning techniques can help. Accordingly, finance, statistics, and data analytics go hand in hand. The purpose of this book is to bring the state-of-art research in these three areas to the fore and especially research that juxtaposes these three.
Keywords: 650; Big data analytics; Advanced statistics; Time series; Panel data analysis; Financial engineering; Risk management in finance; Financial institutions